1988
DOI: 10.1002/jbmr.5650030311
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of serum parathyroid hormone and ionized calcium concentrations during reproduction in rats fed a low calcium diet

Abstract: Moderate dietary restriction of calcium (0.1% Ca) was used to accentuate the changes in serum immunoreactive parathyroid hormone (iPTH) that had been reported earlier in lactating rats fed 0.4% Ca diet. In addition, the effects of this low-Ca diet on serum total and ionized Ca and iPTH during pregnancy, extended lactation, and weaning were examined. The positive correlation between serum total and ionized Ca was highly significant (r = 0.88, p less than 0.001, n = 120). Serum iPTH was significantly higher (36%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This may be especially true in rats where the hourly fetal demand for calcium almost equals the amount of calcium present in the maternal circulation (196). Consistent with this, increased litter number and weight are associated with a lower serum calcium in the mother (90), while pregnant rats fed a low-calcium (0.1%) diet experienced a marked decline in both serum calcium and ionized calcium during the last several days before delivery (321). A low-calcium diet similarly provoked hypocalcemia in pregnant ewes compared with consumption of a usual and a high-calcium diet (69).…”
Section: Calcium and Phosphorusmentioning
confidence: 75%
See 2 more Smart Citations
“…This may be especially true in rats where the hourly fetal demand for calcium almost equals the amount of calcium present in the maternal circulation (196). Consistent with this, increased litter number and weight are associated with a lower serum calcium in the mother (90), while pregnant rats fed a low-calcium (0.1%) diet experienced a marked decline in both serum calcium and ionized calcium during the last several days before delivery (321). A low-calcium diet similarly provoked hypocalcemia in pregnant ewes compared with consumption of a usual and a high-calcium diet (69).…”
Section: Calcium and Phosphorusmentioning
confidence: 75%
“…The serum calcium of lactating rats has been quite variable in published reports, and not clearly explained by the calcium content of the diet: hypercalcemia on 1.5 or 1.2% calcium (86,318); normocalcemia on 1.6% (568), 1% (991), 0.5% (114), 0.4% calcium (91,318,569), and an unspecified diet (337); low blood calcium on 1.2, 0.9, 0.8, and 0.4% calcium (76,90,320,321,568,718,920,927,989); and marked hypocalcemia on 0.1, 0.04, and 0.01% calcium (32,320,321,568,991). The ionized calcium has been low on a 1.6% calcium diet (568), high on a 1.2% calcium diet (318), low on a 0.8% calcium diet (989), normal (318) and low on a 0.4% calcium diet (90,568,569), and low on a 0.1% calcium diet (32, 568).…”
Section: Calcium and Phosphorusmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Meissonier et al (1980) and Lingaas et al (1992), plasma Ca of sows decreased with progressing parity, which was confirmed by Liesegang et al (2005) and which is consistent with the observations in study 1. Likewise in the rat, plasma Ca has been reported to decrease during the last several days of pregnancy (Garner et al, 1988). Kovacs and Kronenberg (1997) suggested that maternal losses of Ca to a litter of rapidly growing fetuses probably exceed the maternal Ca stores (Garel, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, hormonal regulation undergoes adaptive changes. This particularly applies to parathormone, calcitriol, and calcitonin (GARNER et al 1988; DE ROUFFIGNAC & QUAMME 1994;DAI et al 2001;HUBERT et al 2007;MUSCHER et al 2008). In pregnant women, blood plasma concentrations of parathormone and calcitonin do not differ significantly from those observed in non-pregnant women (ARDAWI et al 1997;MESTMAN 1998;PRENTICE 2000), whereas the level of calcitriol increases more than twofold.…”
mentioning
confidence: 98%